2015
DOI: 10.1515/hf-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

A light-colored hydroxypropyl sulfonated alkali lignin for utilization as a dye dispersant

Abstract: A light-colored hydroxypropyl sulfonated alkali lignin (HSAL) was synthesized based on pine alkali lignin (AL) by grafted-sulfonation and crosslinking reaction processes. The reactions were evaluated by gel-permeation chromatography (GPC), infrared (IR) and proton nuclear magnetic resonance ( 1 H-NMR) spectroscopy. The sulfonic group content and the molecular weight ( M w ) of HSAL significantly increased, while the phenolic hydroxyl groups diminished by around 80% compared to AL. The color of HSAL turned to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Lignin is the second largest natural polymer, after cellulose in plants, on earth. Especially, over 50 million tons of industrial lignin is produced from the paper-making industry as a byproduct every year. , However, only 2% of lignin is effectively unitized; more than 98% of lignin is combusted as fuel, which not only causes environmental problems but also causes huge waste of the resources. Therefore, research on value-added application for lignin is considerably meaningful for the development of renewable resources. In recent years, lignin-based optical materials have been reported. Qian et al reported lignin-based colloidal nanospheres with potential application in the field of sunscreen. Bula et al reported a novel functional silica/lignin hybrid material, and it could improve the elongation at break and notched impact strength of polypropylene.…”
Section: Introductionmentioning
confidence: 99%
“…Lignin is the second largest natural polymer, after cellulose in plants, on earth. Especially, over 50 million tons of industrial lignin is produced from the paper-making industry as a byproduct every year. , However, only 2% of lignin is effectively unitized; more than 98% of lignin is combusted as fuel, which not only causes environmental problems but also causes huge waste of the resources. Therefore, research on value-added application for lignin is considerably meaningful for the development of renewable resources. In recent years, lignin-based optical materials have been reported. Qian et al reported lignin-based colloidal nanospheres with potential application in the field of sunscreen. Bula et al reported a novel functional silica/lignin hybrid material, and it could improve the elongation at break and notched impact strength of polypropylene.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in TSI means that particle sedimentation was fast and the thickness of sediment was increased. Therefore, a high TSI value means that a suspension had a low stability. ,, The TSI of a blank graphite suspension (without dispersant) increased rapidly with time to approximately 40 after 140 min (Figure ). The very high TSI value of the blank suspension suggests graphite particles were unstable and rapid sedimentation took place due to aggregation (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Another biorefinery sodium LS (Na-LS-LP) was directly separated from the freely drainable spent liquors (Figure 1) of SPORL pretreated mountain pine beetle killed lodgepole pine (BKLP) through dialysis as described previously. 21 The liquors were first centrifuged at 4000 rpm for 20 min to remove solids. Two membranes ES404 and FP200 (Xylem PCI Membranes, Kostrzyn, Poland) with cutoff molecular weight of 4 and 200 kDa, respectively, were used to remove low molecular weight impurities such as sugars and sugar degradation products (furans and organic acids, etc.)…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several methods that can be used for activation or modification of these groups. Modification can be carried out by acidolysis [ 10 , 11 ], acetylation [ 12 , 13 ], alkylation [ 14 , 15 ], halogenation [ 16 , 17 ], nitration [ 18 , 19 ], sulfonation [ 20 , 21 ] and ozonolysis [ 22 , 23 ]. Another way of increasing lignin’s reactivity is the selective oxidation of β- O -4 linkages using nitrobenzene [ 24 , 25 , 26 ], potassium permanganate [ 27 , 28 ], sodium periodate [ 29 , 30 ] or hydrogen peroxide [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%